Life skills : how to do almost anything - Chicago Tribune (Firm) (2013)
"A collection of articles from the Chicago Tribune's 'Life Skills' column"--
Keywords: Life skills -- Handbooks, manuals, etc; Home economics -- Handbooks, manuals, etc; Etiquette